Fine-scale population genetic structure of Endangered Caspian Sea trout, Salmo caspius: implications for conservation - Tabatabaei, Seyedeh Narjes; Abdoli, Asghar; Hashemzadeh Segherloo, Iraj; Normandeau, Eric; Ahmadzadeh, Faraham; Nejat, Farshad; Bernatchez, Louis (Hydrobiologia, 2020)
Many populations of Caspian Sea trout ( Salmo caspius )—a nationally endangered species in Iran—have been extirpated or depleted due to anthropogenic impacts. The Lar National Park hosts large populations of Caspian Sea trout, which have not been subject to fisheries management programs before, but the population/s also face different human-related threats that may endanger their sustainability. A total of 357 Caspian Sea trout collected from different streams in Lar National Park were genotyped at 7978 filtered SNP using Genotyping-By-Sequencing to document population genetic structure and the contribution of each population/habitat to lake-run trout fisheries. Our results revealed a fine-scale population genetic structure, which is probably a product of factors including natural and artificial barriers to gene flow, geographic distance, and behavioral differences between resident and lake-run trout. Mixed-Stock Analyses revealed a high contribution from four panmictic populations of the national park to lake-run fish and almost no contribution from streams located in upper reaches or from streams with hydro-chemical or physical barriers. Our results highlighted the necessity for a more serious conservation plan for both the populations contributing greatly to lake fisheries and the highly diverged upstream populations due to their uniqueness.